FRI0452 Nailfold capillaroscopy in antisynthetase syndrome (NASCAR): results of a multicenter, international study of the american and european network of antisynthetase syndrome (AENEAS). (12th June 2018) - Sebastiani, M.; Triantafyllias, K.; Manfredi, A.; González-Gay, M.A.; Palmou-Fontana, N.; Cassone, G.; Drott, U.; Delbrück, C.; Rojas-Serrano, J.; Bertolazzi, C.; Nuño, L.; Giannini, M.; et al.
Abstract : Background: Antisynthetase syndrome (ASSD) is an autoimmune disease characterised by the clinical triad arthritis, myositis, and interstitial lung disease (ILD). Despite Raynaud's phenomenon (RP) is another typical feature of ASSD, nailfold videocapillaroscopy (NVC) assessment of these patients has been only sporadically described, without the elucidating data for clinicians. Objectives: To describe NVC features of ASSD patients and to investigate possible correlations with clinical and serological features of the disease. Methods: We retrospectively analysed NVC images of 190 ASSD patients (females/males 3.76, mean age 49.7±12.8 years, mean disease duration 51.2±71.4 months, 133 anti-Jo-1 and 57 non-anti-Jo-1 positive patients). For each patient, we examined number of capillaries, giant capillaries, micro-haemorrhages, avascular areas, ramified capillaries, and the presence of scleroderma (SSc) patterns. Finally, we correlated NVC features with clinical and serological findings of ASSD patients. Results: NVC abnormalities were observed in 62.1% of AASD patients compared with 29.3% of a group of 75 patients with primary Raynaud's phenomenon (p<0.001). A SSc-like pattern was detected in 67 (35.3%) patients and it was associated with anti-Jo-1 antibodies (p=0.002) and also with a longer disease duration (p=0.004). Interestingly, there was no significant correlation between the presence of SSc-like pattern and RP, and only 47% of patients with SSc-like pattern had RP. Conclusions: NVC abnormalities are commonly observed in ASSD, independently to the occurrence of RP. The presence of a SSc-like pattern should let to identify a more defined ASSD subtype and prospective studies could confirm the association with clinical and serological features of ASSD. Disclosure of Interest: None declared